Financial Sustainability of the Russian Higher Education Institutions: Quantitative Analysis - D. A. Endovitsky; V. V. Korotkikh; A. V. Krivosheev (Высшее образование в России)
Purpose. Quantitative analysis and identification of determinants of Russian universities’ financial sustainability.Methods. Non-parametric methods for data analysis and machine learning.Results. We proposed two groups of working hypothesis. The levels of financial sustainability of Russian state universities are linked to internal environmental factors including the levels of financial management quality, income-generating activities scale, debt financing, fiscal discipline, academic and research-based activities scales. The levels of financial sustainability of Russian state universities are linked to external environmental factors and depend on the funding patterns and regional dimensions.Conclusions. Special conditions for increased state funding are not sufficient to strengthen universities’ financial sustainability. Moreover, we have established the insignificance of the university geographical location influence on financial sustainability. We have come to a conclusion that both financial management efficiency and prior year financial sustainability have key roles to play in current sustainability formation. Universities with a large scale of income-generating activities are more financially stable due to the diversification of sources of financial support for their overall activities.